EFEKTIVITAS PENERAPAN MODEL RECIPROCAL TEACHING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA - Pertiwi, Peni; Elindra, Rahmatika; Ahmad, Marzuki (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Abstract This study aims to determine the effectiveness of the application of the Reciprocal Teaching model on the mathematical critical thinking skills of MTs students. Al-Abraar. This type of research is experimental research, with the entire population of class VIII MTs students. Al-Abraar as many as 102 students. The sample of this research is class VIII C, totaling 28 students using simple random sampling technique. Data collection uses observations and tests that have been previously validated. The results showed an overview of the reciprocal teaching learning model with an average value of 3.30 with a